Pengaruh Investasi Penanaman Modal Terhadap Pertumbuhan Ekonomi Melalui Peningkatan Produk Domestik Bruto di Indonesia - Alice; Ekklesia; Lena Sepriani; Yohana Juwitasari Hulu (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2021)
Economic growth is very important for all countries, one way that can be done to increase economic growth is to invest both domestic investment (PMDN) and foreign investment (PMA). The purpose of this study to analyze the effect of investment on Indonesia's economic growth through an increase in gross domestic product. This research is quantitative research with the using of secondary data from Central Bureau of Statistics Republic of Indonesia. The data were analyzed using multiple regression methods. The results showed that foreign investment and domestic investment basically increased gross domestic product, but in this study foreign investment did not significantly affect gross domestic product. On the other hand, domestic investment has a significant effect on gross domestic product.